IMPLEMENTATION OF DIGITAL FLASHCARD LEARNING MEDIA TO INCREASE VOCABULARY MASTERY OF 8TH GRADE STUDENTS AT SMP LABORATORIUM UNDIKSHA - Raspadewi, Ni Luh Putu Diah; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This research investigates the effectiveness of the implementation of digital flashcard learning media in improving vocabulary mastery among 8th grade students at SMP Laboratorium Undiksha. The design of this research is quasi-experimental with pre test for both control and experimental group. The sample of this study is two classes with each 26 and 25 students, 51 students in total. The findings revealed a notable improvement in the post test score of experimental group, with the mean score of 81.72 which is higher compared to the post test mean score of the control group which is 72.40. Moreover, independent sample t-test result indicates that the score is statistically significant, further supported by the result of Cohen’s d effect size that demonstrated the strong effect of digital flashcard towards vocabulary mastery. These findings signifies the effectiveness of digital flashcard as an engaging and interactive learning media to address the challenges of vocabulary mastery in English as a foreign language, particularly in the context of urban school with access to adequate technology.